ENVIRONMENTAL INFLUENCES ON THE INCIDENCE OF ACUTE RESPIRATORY INFEKTION IN TODDLERS (At Hamlet Village Wonokerto Peterongan Jombang) - Rahmawati Deny Andrian; Evi Rosita; Dwi Prasetyaningati (STIKES Insan Cendekia Medika Jombang, 2012)
Based on the profile of Jombang District Health Office in 2012 the incidence of acute respiratory infection ininfants is quite high as many as 5584 cases. While the data from health centers Peterongan AcuteRespiratory Infektion was ranked third type of disease Peterongan outpatient health centers. AcuteRespiratory Infektion patients toddler discovery in 2012. Acute Respiratory Infektion is a disease basedunhealthy environment. This study was conducted to determine the effect of the environment on the incidenceof Acute Respiratory Infektion in Toddlers at Hamlet Village Wonokerto Peterongan Jombang. This type ofresearch is analytic korelational. The study population was 56 respondents. Sampling technique usespurposive sampling number 49, the study carried out on 30 July 2012. The independent variable is theenvironment and the dependent variable was the incidence of Acute Respiratory Infektion. The researchinstrument used was a questionnaire. Then analyzed with editing, coding, scoring, tabulating and statisticalchi square test with error level p = 0.000. The results showed that the effect of largely healthy environment.While the incidence of Acute Respiratory Infektion have a negative impact. And on positive criteria AcuteRespiratory Infektion 48.9%, and 51.0% negative, significant results obtained by ρ = 0.000 environment withAcute Respiratory Infektion or less than α = 0.005 so that it can be stated that H1 is accepted or no effectbetween environmental influences with the incidence of acute respiratory infection in infants in DusunWonokerto Village Peterongan Jombang. The conclusion of the study showed that there is influence ofenvironment on the incidence of Acute Respiratory Infektion in Hamlet Village Wonokerto PeteronganJombang.Health workers are expected to further improve education on a healthy environment to the patient so that thepatient Acute Respiratory Infektion understand about reducing the risk of Acute Respiratory Infektionprogram schedule existing health centers.